Harvest index and evolution of major food crop cultivars in the tropics - Kawano, K (Springer, 1990)
Relative importance of harvest index (I) and total biomass yield (B) to economic yield (Y) was assessed in several food crops at different levels of environmental productivity. Importance of B is generally higher in low than high yielding environments, while that of I is higher in high than low yielding environments. In some crops B is important throughout different yield levels while in others I is important even in low yielding environments. Past efforts by anonymous farmers have consummated a good part of genetic improvement of crop yields through improvement in B. Many venerable land cultivars of grain crops, adapted to unimproved, limited-input cultural conditions, evolved through this process. The same process may not have thoroughly exhausted the yield improvement opportunity through improving I. Success in yield improvement by modern breeding has been limited mainly to high-input cultural conditions characterized by higher soil fertility and irrigation mainly through improvement in I. Varietal improvement possibility for less productive environments is discussed.